Math, asked by krishnayadav61, 1 year ago

using crossmultiplication method solve the equation ax+by=a-b; bx-ay=a+b

Answers

Answered by Azfer
2

Answer:


Step-by-step explanation:

ax + by = a-b becomes

(ax + by)/(a - b) = 1


bx - ay = a + b becomes

(bx-ay)/(a+b) = 1


So now we can equate the two:


(ax + by)/(a-b) = (bx - ay)/(a+b)

So by cross multiplication:

(ax + by)(a + b) = (bx - ay)(a - b)

a^2x + abx + aby + b^2y = abx - b^2x - a^2y + aby

a^2x + b^2y = -b^2x - a^2y

a^2x + b^2x = -a^2y - b^2y

(a^2 + b^2)x = -(a^2 + b^2)y

x = -y

Substituting into the first equation:

-ay + by = a-b

-(a - b)y = a-b

y = -1

So x = 1


To check: a(1) + b(-1) = a-b, b(1) - a(-1) = a + b


Read more on Brainly.in - https://brainly.in/question/2419020#readmore

Similar questions